Mycophagy in the yellow-footed tortoise (Chelonoidis denticulatus): feeding trial experiments at Tijuca National Park (Rio de Janeiro, Brazil) - Larissa Trierveiler-Pereira; Emily dos Santos Silva; Carolina Starling-Manne; Juliano M. Baltazar (Lilloa, 2025)
The act of consuming any part of fungi is termed mycophagy. Certain basidiomes contain highly nutritious elements, such as proteins, vitamins, and minerals, which can be extremely valuable in the animal diet. Mycophagous behavior in animals is well-documented in ethological studies; however, due to the scarcity of macrofungi experts in Brazil, the fungal species consumed are often not identified. The Tijuca National Park (TNP) is a fragment of the Atlantic Forest located in the city of Rio de Janeiro (Brazil), covering an area of 3,953 hectares. The Refauna Association works within TNP to restore ecological interactions in the area through the reintroduction of vertebrate species previously present in the region. One of the reintroduced species is the yellow-footed tortoise (Chelonoidis denticulatus), a terrestrial chelonian. Several studies have documented the mycophagous behavior of chelonians; however, it is important to emphasize the lack of studies dedicated to identifying the fungal species comprising their diet. In November 2021, cafeteria-style feeding trials were conducted with Refauna’s yellow-footed tortoises, in which they were offered the macrofungi collected from TNP were offered to the animals. A total of 21 basidiomycete specimens representing 13 taxa, were collected and offered. The morphology of the offered macrofungi was highly diverse, including agaricoid mushrooms, jelly fungi, gasteroid fungi (earthstar and sequestrate form), and coralloid fungi. The macrofungi were offered to seven individual tortoises, and only one rejected the offered mushrooms. Basidiomes from ten species were consumed by the tortoises, while three were either rejected or only partially accepted.